2013
DOI: 10.1021/ja409609j
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into DNA Replication without Hydrogen Bonds

Abstract: The genetic alphabet is comprised of two base pairs, and the development of a third, unnatural base pair would increase the genetic and chemical potential of DNA. d5SICS-dNaM is one of the most efficiently replicated unnatural base pairs identified to date, but its pairing is mediated by only hydrophobic and packing forces, and in free duplex DNA it forms a cross-strand intercalated structure that makes its efficient replication difficult to understand. Recent studies of the KlenTaq polymerase revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 53 publications
5
86
1
3
Order By: Relevance
“…In contrast, addition of d NaM TP to a complex of KlenTaq bound to template containing d 5SICS does not fully induce the formation of the catalytically competent closed state. [167] However, it does induce the formation of a partially closed state, in which d 5SICS moves toward the insertion site and d NaM TP is bound to the O-helix via its triphosphate moiety. This state is similar to the ajar state, which is thought to allow the polymerase to test for correct base pairing during the synthesis of natural DNA.…”
Section: Structural Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, addition of d NaM TP to a complex of KlenTaq bound to template containing d 5SICS does not fully induce the formation of the catalytically competent closed state. [167] However, it does induce the formation of a partially closed state, in which d 5SICS moves toward the insertion site and d NaM TP is bound to the O-helix via its triphosphate moiety. This state is similar to the ajar state, which is thought to allow the polymerase to test for correct base pairing during the synthesis of natural DNA.…”
Section: Structural Studiesmentioning
confidence: 99%
“…[167] While structural differences were observed, in each case the UBP was positioned in the correct post-insertion site, where it again assumed an intercalated structure as it does in the free duplex.…”
Section: Structural Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1A) being a particularly promising example (5-7). Despite lacking complementary hydrogen bonding, we demonstrated that the dNaM-d5SICS UBP is well replicated by a variety of DNA polymerases in vitro (7-10), and that this efficient replication is mediated by a unique mechanism that draws upon interbase hydrophobic and packing interactions (11,12). These efforts then culminated in the first progress toward the creation of an SSO in 2014, when we reported that Escherichia coli grown in the presence of the corresponding unnatural nucleoside triphosphates (dNaMTP and d5SICSTP), and provided with a plasmid-encoded nucleoside triphosphate transporter (NTT2) from Phaeodactylum tricornutum (which we denote as PtNTT2) (13), is able to import the unnatural triphosphates and replicate a single dNaM-d5SICS UBP on a second plasmid (14).…”
mentioning
confidence: 99%
“…One of the most interesting discoveries identified an “ajar” BF conformation in the presence of a mismatched dNTP; the position of the active site’s O helix is intermediate between the “open” and “closed” states via a kink at residue G711 (Figure 1) [13]. Complexes with rare tautomers of incoming dNTPs [22], bulky dNTP analogs [14], and unnatural base pairs [15,16] also resulted in an “ajar” conformation. Taken together, these results indicate that various structures of polymerases can accommodate binding, but not catalysis, of some non-cognate substrates, and the resultant ajar conformations represent frozen states along the pathway for nucleotide discrimination.…”
Section: Crystallography Provides Insight With Static Visualizationmentioning
confidence: 99%